16S rRNA gene sequencing of non-lactic acid bacteria cultures from lait caillé in Burkina Faso - Geoffroy Romaric Bayili; Clarisse S. Compaoré; Bréhima Diawara; Lene Jespersen; Hagretou Sawadogo-Lingani (All Life)
Diverse species of lactic acid bacteria (LAB) are involved in the spontaneous fermentation of lait caillé, a traditional milk product from Burkina Faso. However, there is little information on the identity of the non-LAB occurring in the fermentation. The objective of this study was to provide information on the identity of non-LAB originating from traditional lait caillé and capable of growing abundantly on standard media used for dairy LAB isolation. Man Rogosa Sharp (MRS) and M17 agar plates previously inoculated with traditional lait caillé were used to screen for gram-negative (catalase-positive or -negative) and gram-positive catalase-positive bacteria. Pure colonies were selected, then the penta-GTG oligonucleotide (GTG)5-based rep-PCR fingerprinting followed by cluster analysis and sequencing of the 16S rRNA gene was performed to identify the isolates. These data will provide key information on the presence of bacteria associated with emerging public health risks. In addition, they may provide insights for a broader investigation of non-LAB occurring in the fermentation of unpasteurized milk and for selective media development.